1988
DOI: 10.1002/eji.1830181131
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of protooncogenes during stimulation of normal human B lymphocytes

Abstract: Protooncogenes play important roles in the regulation of growth and differentiation of normal cells. In this study we have examined the cell cycle-dependent regulation of transcription of various protooncogenes after stimulation of human peripheral blood B lymphocytes. The transcriptional rate of various genes was determined by means of a nuclear run-on assay. We found that several protooncogenes were transcriptionally activated after stimulation (myc, p53, K-ras, H-ras, sis and ets), but with different kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Our data suggest an important amplification role of 1176 in IgE synthesis induced by IL-4 and CD40 engagement . Interestingly, both IL4 and anti-CD40 mAb induced 11,6 production in B cells (9,11) . Furthermore, IL6 increases the phosphorylation of CD40 in human B cells, thus leading to a CD40-IL6 loop (9) .…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggest an important amplification role of 1176 in IgE synthesis induced by IL-4 and CD40 engagement . Interestingly, both IL4 and anti-CD40 mAb induced 11,6 production in B cells (9,11) . Furthermore, IL6 increases the phosphorylation of CD40 in human B cells, thus leading to a CD40-IL6 loop (9) .…”
Section: Resultsmentioning
confidence: 99%
“…during development (Ohlsson et al, 1981; L.Holmgren, R.Glaser, S.Pfeifer-Ohlsson and R.Ohlsson, in preparation). However, in comparison to many genes, which are regulated in a strictly limited cell type-specific manner via enhancer elements, the c-sis gene is expressed by a wide range of cell lineages, although this occurs in very specific spatial and temporal 'windows' for these cell types Smeland et al, 1988;Ohlsson et al, 1991). For this reason, it is perhaps not surprising that the control mechanisms involved in the regulation of c-sis expression appear more complex and diverse than those associated with genes which are more strictly and simply limited to a specific cell type (or types).…”
Section: Discussionmentioning
confidence: 99%
“…G-loop formation will prolong denaturation of the DNA duplex, and thereby increase the probability of AID attack. Like the S regions, c-MYC is transcribed upon B-cell activation (Cole, 1986;Smeland et al, 1988); and it contains distinctly G-rich regions on the nontemplate DNA strand. This suggested that structures might form within the transcribed c-MYC gene and promote interactions with AID, thereby contributing to translocation or aberrant hypermutation of c-MYC in germinal center B cells.…”
Section: Introductionmentioning
confidence: 99%